Walking in Two Directions at Once: Locomotion Techniques in Virtual Environments - Schaefer, Benjamin (Academic Quarter | Akademisk kvarter, 2019)
Walking constitutes a fundamental method for traversing virtual environments, i.e. pressing buttons as an abstracted way to move around such as in videogames. With the second advent of virtual reality devices, virtual walking has gained traction and is gradually becoming a more embodied experience. The ability of virtual reality hardware systems to rudimentarily track the human body allows us to explore a virtual space by physically walking through it. Room-Scaling creates a direct mapping between our bodily movements in the physical room and our corresponding virtual movements. Another technique called Redirected Walking takes virtual walking a step further by disengaging the physical from the virtual space – theoretically – providing the opportunity to virtual walk infinitely in a finite physical space. Based on my research with virtual reality developers, I explore the ideas behind different locomotion styles such as Teleportation and Redirected Walking and the ways developers use and trick our perception to create believable virtual walking and locomotion methods.